Difference Between the Power Consumption Rate of Pre-Paid and Post-Payment Customers: 900 Volt Ampere - Mursyidin, Mursyidin; Syakir, Muhammad; Husnizar, Husnizar (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Both the pre-paid KWH meter and the KWH meter after payment are instruments that PT. Perusahaan Listrik Negara (Persero), also often abbreviated PLN, uses to determine the printing number of KWH meters used by energy users. There is a problem with smart meters in society; many still have doubts about using them because they are thought to be more expensive. In the village of Alue Ie Mameh, the study is to determine the extent of variation in electricity consumption and the computation of electricity prices for pre-paid and post-payment clients over the course of a month of use. The mix method is the strategy. Ten pre-paid consumers and ten post-payment customers were polled by Objects. In the village of Mameh, post-paying customers use more electricity than pre-paid customers do. The longest-running electrical device used by residents of Alue Ie Mameh is their refrigerator, which operates around the clock.